Simplify. Idenfy and x-values for which the expression is undefined.

3x^2-9x-12 / 6x^2+9x+3

(3x^{2}-9x-12) /( 6x^{2}+9x+3)= (3x^{2}-12x+3x-12)/[ ( 6x^{2}+6x+3x+3)]

= [3x(x-4)+3(x-4)]/[6x(x+1)+3(x+1)]

=[(x-4)(3x+3)]/[(6x+3)(x+1)]

If x not equal to -1 , this becomes 3(x-4)/(6x+3)

This is not defined for x= -1/2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up